The Labor Market for Registered Nurses: A Three-Equation Model - Benham, Lee (The Review of Economics and Statistics, 1971)
A BETTER understanding of the professional labor market for registered nurses is important as it relates to current concerns about the rapidly increasing demand for and cost of medical care and the alleged shortage of registered nurses and other medical personnel. In addition, investigation of this market may help to further knowledge about the labor market in general, since registered nurses have a number of characteristics in common with various expanding sectors of the labor force: they constitute a profession, at present over 98 per cent are female, and their work is in the service sector. This study investigates factors influencing the number of employed registered nurses and their earnings across states. Several aspects of simultaneous response patterns in this labor market are examined by use of a simple model which includes one structural equation for demand, one for labor force participation, and one for geographical location. Specific aspects of labor force behavior, such as migration or labor force participation, have been examined in many earlier studies, but few efforts have been made to estimate the interaction of labor market responses. Models of the type developed here, if they successfully incorporate the principal structural relationships within a labor market, can allow examination of a whole range of issues in more precise terms than has been possible previously. For the market investigated here, these include the effects of shifting patterns of demand for medical services, changes in the supply of substitutes for registered nurses, increases in the number of nursing schools, and so forth. For a priori specification of the individual structural equations, existing theory and past studies on demand functions, labor force participation, and migration were used, but these were not sufficient to give very precise guidelines. Therefore, several alternative plausible forms of each equation were initially estimated using cross-sectional data by states for 1950.' In general, the coefficients were not very sensitive to the variations in specification examined. The complete model composed of selected forms of the individual structural equations was then estimated by three-stage least-squares, using the 1950 data. A number of variants of the model were considered for 1950, and the model was found to be fairly robust. As one test of the stability of the cross-sectional relationships, the parameters were then re-estimated using data for 1960.